2022
DOI: 10.15403/jgld-4341
|View full text |Cite
|
Sign up to set email alerts
|

Serum Galectin-3 in Hepatitis C Virus Infection Declines after Successful Virus Eradication by Direct-Acting Antiviral Therapy

Abstract: Background and Aims: Serum galectin-3 is regarded as an inflammatory marker in patients with chronic liver diseases. Hepatitis C virus (HCV) infection is associated with higher levels of inflammatory molecules which ameliorate by efficient treatment with direct-acting antivirals (DAAs). The aim of this study was to compare serum galectin-3 levels between HCV patients before treatment with DAAs and at the time of sustained virologic response at 12 weeks post-treatment (SVR12). Methods: Hepatitis B and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Galectin-3 was also shown to upregulate antiviral genes to inhibit influenza A virus replication [138]. Moreover, galectin-3 expression is induced in immune cells infected by HIV or human T lymphotropic virus type I [138] and upregulated in the serum of HCV-infected patients [138,143]. While the consequences of infection-related elevation of galectin-3 levels remain to be fully understood, galectin-3 upregulation enhanced inflammatory cytokine levels and myofibroblast activation, both with roles in lung fibrosis [144].…”
Section: Galectin-3mentioning
confidence: 99%
“…Galectin-3 was also shown to upregulate antiviral genes to inhibit influenza A virus replication [138]. Moreover, galectin-3 expression is induced in immune cells infected by HIV or human T lymphotropic virus type I [138] and upregulated in the serum of HCV-infected patients [138,143]. While the consequences of infection-related elevation of galectin-3 levels remain to be fully understood, galectin-3 upregulation enhanced inflammatory cytokine levels and myofibroblast activation, both with roles in lung fibrosis [144].…”
Section: Galectin-3mentioning
confidence: 99%
“…Concerning the role of galectin-3 in viral infections, it can participate in interactions taking place between virus and host during viral entry, viral replication, or immune response modulation [7]. Hepatitis C virus infection increases serum galectin-3 levels, which in turn can promote inflammation and fibrosis progression [22]. Galectin-3 is also suggested to play a role in the early stages of human immunodeficiency virus (HIV) infection by enhancing viral entry [23].…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 has also been implicated in HCV infection. Research comparing serum levels of Gal-3 in HCV patients before and after treatment with direct-acting antivirals (DAAs) has shown that HCV infection increases serum Gal-3 levels, which may contribute to inflammation and fibrosis progression [96]. However, successful DAA treatment reduces serum Gal-3 levels, suggesting a potential role for Gal-3 in monitoring HCV treatment outcomes [96].…”
Section: Galectin-3 and Hepatitis C Virus Infectionsmentioning
confidence: 99%